2019
DOI: 10.1021/acs.energyfuels.8b04413
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Microbiota Communities with the Ranks of Coals from Three Permian Mining Areas

Abstract: Microorganisms play vital roles in the biogeochemical processes, such as biomethane production, which is an important source of coal bed methane (CBM), that occur in coal beds. However, little information is available regarding the microbial communities in in situ coal beds of different ranks from Permian mining areas. In this study, anaerobic Biolog ECO microplates were used to determine the microbial metabolic activity, and high-throughput sequencing was used to investigate the bacteria and archaea communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Our previous study 5 found that soluble carbon sources had stimulative effects on microbial diversity in different coal samples. Bucha et al 34 also found that various nutrients stimulated microbial activity and further increased coal methanogenic capacity.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Our previous study 5 found that soluble carbon sources had stimulative effects on microbial diversity in different coal samples. Bucha et al 34 also found that various nutrients stimulated microbial activity and further increased coal methanogenic capacity.…”
Section: Discussionmentioning
confidence: 93%
“…After hundreds of millions of years of biochemical and geological processes, nutrients in coal seams are depleted, and low nutrient availability limits microbial activity and function; however, the infiltration of soil extraction can provide a large amount of nutrients and inorganic salts to microorganisms in a relatively short time. Our previous study found that soluble carbon sources had stimulative effects on microbial diversity in different coal samples. Bucha et al also found that various nutrients stimulated microbial activity and further increased coal methanogenic capacity.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations